Students learned knowledge of the concept of angle and angular measure: A didactic transposition perspective - Herizal; Priatna, Nanang; Prabawanto, Sufyani; Jupri, Al (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
The concept of angle and angular measure are essential concepts that need to be well understood in learning geometry. However, students often misunderstand these concepts. This study aimed to analyze how the shift in knowledge of the concept of angle and angle measurement in the perspective of didactic transposition. A qualitative study with a phenomenological approach was conducted to examine this phenomena. Data were collected through classroom observation, interviews, and documentation studies. The results of the study indicate that the transposition process in learning affects students' conceptualization process of the definition of angles so that students cannot distinguish between angles and anglular measure and tend to consider the two to be the same. A weak transposition process often causes errors, variations in meaning, and limited knowledge. This study emphasizes the need for a good didactic approach to bridge the gap in the transition process between scientific knowledge of mathematics and students' understanding. The implications of this study suggest that there is an alignment of both the curriculum and teaching materials that are in line with scholarly knowledge to improve students' understanding of the concept of angles and anglular measure.